Whole exome sequencing of patients with varicella-zoster virus and herpes simplex virus induced acute retinal necrosis reveals rare disease-associated genetic variants - Heinz, Johanna L.; Swagemakers, Sigrid M. A.; von Hofsten, Joanna; Helleberg, Marie; Thomsen, Michelle M.; De Keukeleere, Kerstin; de Boer, Joke H.; Ilginis, Tomas; Verjans, Georges M. G. M.; van Hagen, Peter M.; van der Spek, Peter J.; Mogensen, Trine H. (Frontiers in Molecular Neuroscience, 2023)
Purpose Herpes simplex virus (HSV) and varicella-zoster virus (VZV) are neurotropic human alphaherpesviruses endemic worldwide. Upon primary infection, both viruses establish lifelong latency in neurons and reactivate intermittently to cause a variety of mild to severe diseases. Acute retinal necrosis (ARN) is a rare, sight-threatening eye disease induced by ocular VZV or HSV infection. The virus and host factors involved in ARN pathogenesis remain incompletely described. We hypothesize an underlying genetic defect in at least part of ARN cases. Methods We collected blood from 17 patients with HSV-or VZV-induced ARN, isolated DNA and performed Whole Exome Sequencing by Illumina followed by analysis in Varseq with criteria of CADD score > 15 and frequency in GnomAD < 0.1% combined with biological filters. Gene modifications relative to healthy control genomes were filtered according to high quality and read-depth, low frequency, high deleteriousness predictions and biological relevance. Results We identified a total of 50 potentially disease-causing genetic variants, including missense, frameshift and splice site variants and on in-frame deletion in 16 of the 17 patients. The vast majority of these genes are involved in innate immunity, followed by adaptive immunity, autophagy, and apoptosis; in several instances variants within a given gene or pathway was identified in several patients. Discussion We propose that the identified variants may contribute to insufficient viral control and increased necrosis ocular disease presentation in the patients and serve as a knowledge base and starting point for the development of improved diagnostic, prophylactic, and therapeutic applications.